A Post-Operative Follow-Up of an Endangered Saltwater Fish Lensectomy for Cataract Management in a Public Aquarium: A Case Series - Julie Pujol; Benjamin Lamglait; Maria Vanore; Catherine Rousseau; Claire Vergneau-Grosset (Veterinary Sciences, 2023)
Mature cataracts can be a life-threatening condition in fish as it may result in anorexia. Lens extraction has been previously described in fish, but the long-term outcome of this procedure has not been evaluated. Eleven captive-bred adult fish housed in a public aquarium presented with unilateral (n = 3/11) or bilateral (n = 8/11) mature cataracts. All cases belonged to three endangered fish populations: striped bass (Morone saxatilis) originating from the Saint Lawrence River and Atlantic and spotted wolffish (Anarhichas lupus and Anarhichas minor). Pre-operatively, fish presented with anorexia, dark discoloration, abnormal position in the water column, skin abrasions, and/or decreased body condition scores. A lensectomy was performed in eleven fish, including a bilateral procedure in four fish, corresponding to fifteen eyes. Follow-up examinations were performed one to two weeks and one year post surgery. The main complication was self-resolving: corneal edema was present in 67% of eyes, persistent after a week in 47% of eyes, and resolved thereafter. Post-operatively, 73% of fish resumed feeding and regained a good body condition score. Persistent visual impairment post-surgery associated with anorexia required euthanasia in three out of eleven cases. The median time of death was 336 days post surgery (range: 27–1439 days) and three cases were still alive 1334 to 1425 days after the lensectomy. This was considered a favorable outcome for these older individuals with concurrent diseases.